MERETAS KEBEKUAN IJTIHAD DALAM KONSTRUKSI FIQIH SOSIAL - Sakirman Sakirman (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2015)
To rip up the static Ijtihad in the construction of social jurisprudence. Recently there aremany growing issues to be solved in many sectors such economic, social and culture, within thecontemporary Islamic law. Therefore it is important as mujtahid to be eye catching to see the currentissues and to review the decission law in according to the need of the people. Ijtihad is one of methodsto analyze the islamic law logically and rationally according to the social movement, trying to analyzeand examine the law that should be developed in the society. And it is important to examine thatijtihad is allowed by the scholars. Ijtihad is a dynamic activity which is developing with thedevelopment of the human thought and activities. Though Ijtihad is done for the sake of peoplewelfare but the Mujtahid should consider of deciding the law though two methods, Ijtihad Intiqa’ orInsya’i Ijtihad. When solving the issues one should aware of the ijtihad jam’i and maqasid syar’iyyah.And thus the ijtihad will be able to solve the problem in society.